Topological Engineering of the Iso-Frequency Contours in Connection-Type Metamaterials - Liao, Zhao-Lin; Deng, Wei-Min; Xiang, Ze-Liang; Chen , Wen-Jie; Dong , Jian-Wen (Frontiers in Physics, 2022)
Topology of iso-frequency surface governs the electromagnetic wave propagation and light-matter interaction in metamaterials. For most metamaterials with local medium description, the low-frequency isosurfaces are typical spheres or ellipsoids centered at zero momentum, which in some extent limits our manipulation ability on low-frequency wave. In this work, based on connection-type wire metamaterials, we propose a scheme to engineer the shapes of iso-frequency surfaces. An equivalent circuit model is developed to analyze the low-frequency dispersion of connection-type metamaterials. It implies that the shape of index ellipsoids at quasistatic limit are determined by the equivalent inductances and capacitances of the metallic meshes. By adjusting these equivalent circuit parameters, we can achieve the isotropic or anisotropic index ellipsoids at quasistatic limit and hence a square or bowtie shaped iso-frequency contours for the lowest frequency band. Our results demonstrate a feasible platform for topological engineering of iso-frequency surfaces, which may pave the way to novel devices for manipulating long wavelength electromagnetic wave.